High‐pressure metamorphism in the southern New England Orogen: Implications for long‐lived accretionary orogenesis in eastern Australia. Issue 9 (30th September 2015) - Phillips, G.; Offler, R.; Rubatto, D.; Phillips, D.
Abstract New geochemical, metamorphic, and isotopic data are presented from high‐pressure metamorphic rocks in the southern New England Orogen (eastern Australia). Conventional and optimal thermobarometry are augmented by U‐Pb zircon and 40Ar/39Ar phengite dating to define pressure‐temperature‐time (P‐T‐t) histories for the rocks. The P‐T‐t histories are compared with competing geodynamic models for the Tasmanides, which can be summarized as (i) a retreating orogen model, the Tasmanides formed above a continuous, west dipping, and eastward retreating subduction zone, and (ii) a punctuated orogen model, the Tasmanides formed by several arc accretion, subduction flip, and/or transference events. Whereas both scenarios are potentially supported by the new data, an overlap between the timing of metamorphic recrystallization and key stages of Tasmanides evolution favors a relationship between a single, long‐lived subduction zone and the formation, exhumation, and exposure of the high‐pressure rocks. By comparison with the retreating orogen model, the following links with the P‐T‐t histories emerge: (i) exhumation and underplating of oceanic eclogite during the Delamerian Orogeny, (ii) recrystallization of underplated and exhuming high‐pressure rocks at amphibolite facies conditions coeval with a period of rollback, and (iii) selective recrystallization of high‐pressure rocks at blueschist facies conditions, reflecting metamorphism in a cooled subduction zone. The retreating orogen model can also account for the anomalous location of the Cambrian‐Ordovician high‐pressure rocks in the Devonian‐Carboniferous New England Orogen, where sequential rollback cycles detached and translated parts of the leading edge of the overriding plate to the next, younger orogenic cycle.